Application of Modified Starch on Bioplastic Spoon Based Carrageenan from Eucheuma cottonii on Biodegradability and Water Resistance - Muhammad Dzaky; Laksmi Sulmartiwi; Dwi Yuli Pujiastuti (Journal of Marine and Coastal Science, 2022)
Polysaccharides such as carrageenan are potential materials that can be used as bioplastics. Modified starch is a material that can reduce the hydrophilic properties and increase the hydrophobic and mechanical properties of bioplastics. The purpose of this study was to determine the effect of the application of modified starch on carrageenan-based bioplastic spoons from seaweed Eucheuma cottonii on the biodegradability and water resistance, and to determine the best formulation of bioplastic spoons that could produce the best biodegradability and water resistance. The experimental method in this study used a completely randomized design. The treatment given was the concentration of modified starch (0; 2; 2.5; and 3 grams). The results showed that the addition of modified starch would slow down the rate of biodegradation and improve water resistance, but produced fluctuating values caused by various factors.